Evaluating the contribution of acid resistance systems and probing the different roles of the glutamate decarboxylases of listeria monocytogenes under acidic conditions - Chun FANG; Xiaowei FANG; Xueyang CHEN; Chen WANG; Xiongyan LIANG; Yufang GU; Weihuan FANG; Yuying YANG (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2019)
Listeria monocytogenes is an important zoonotic foodborne pathogen, which can cause a severe invasive illness to susceptible humans and animals with high mortality. As L. monocytogenes is widely distributed in natural environments, the bacterium is easy to contaminate food processing facilities and the products to be ingested by host. But during the transition from a saprophyte to intracellular pathogen, one of the biggest challenge L. monocytogenes encounters is the acid stress. To combat the acidic environments, the bacterium developed several acid resistance systems, including acid tolerance response (ATR), F0F1-ATPase, glutamate decarboxylase (GAD), arginine deiminase (ADI) and agmatine deiminase (AgDI). In this study, we comprehensively evaluated the contributions of different acid resistance systems and explored the different roles of the three GAD components under acidic conditions. We found that the GadD2 of GAD system made the largest contribution to the survival of L. monocytogenes in artificial gastric juice (AGJ) and acidic brain heart infusion (BHI), which was followed by the global stress regulator SigB, GadD3 of GAD system, AguA1 of AgDI system and ArcA of ADI system. Transcription analysis showed that the mRNA level of the three GADs were consistent with their contribution to acid resistance. Similar results were observed in the other three representative strains EGDe, Lm850658 and M7. We further obtained the purified GADs and their poly-antibodies to demonstrate that the contribution of the three GADs were determined by the protein levels in L. monocytogenes. Further studies are needed to focus on the regulation of different expression of the GAD system.